Simulation of Spectral Movement of Vowels using Acoustical Tube - Balbonas, D.; Daunys, G. (Elektronika ir Elektrotechnika, 2009)
A vocal tract can be described using the serially connected electrical circuits of T-type. Its frequency response was obtained by two ways: simulation of the signal and later calculation of the spectrum, and calculation of frequency response of serially connected two-ports. In the first case, a mathematical model of the acoustic tube was built using a state variable approach, where the state variables are capacitor voltages (equivalent to sound pressure) and the inductance currents (equivalent to air volume speed). An obtained system of linear differential equations was integrated by indirect method. In the second case, two-ports “a” parameters were used to obtain all system frequency response. During vowel pronunciation the areas of the vocal tract cross-section are obtaining changes over time. In both methods formant trajectories were extracted from the vocal tract frequency response. The results of both methods were compared. The trajectories of formants are more stable, when they are obtained using a second approach. Ill. 7, bibl. 8, tabl. 1 (in English; abstracts in English, Russian and Lithuanian).